URGENSI LITERASI KESEHATAN MENTAL ISLAMI PADA PENDIDIKAN TINGGI KEAGAMAAN ISLAM (COVID-19) - Putri Anditasari (UIN Sunan Gunung Djati Bandung, 2023)
This research aims to discuss the urgency of Islamic mental health literacy in Islamic Higher Education, where so far the trend of mental problems and suicidal tendencies in students has increased. This mental health literacy from an Islamic point of view in students is still considered low. This research uses a qualitative approach by applying descriptive-analytical methods. The results and discussion of this study indicate that in order to improve Islamic mental health literacy, a special strategy is needed for universities such as utilizing technology, psychoeducation, and including Islamic mental health literacy in the learning curriculum. This study concludes that Islamic mental health literacy in Islamic religious universities is very important because the introduction to Islamic mental health knowledge at the age of transition from adolescence to early adulthood will make students able to deal with problems and pressures in a way that is in accordance with Islamic religious values. Islamic mental health literacy will have an impact on improving student academic achievement, harmonious relationships between students and their environment, and will indirectly help improve the quality of achieving the vision and mission of educational institutions.